3(3x-9)-3=3(x-4)+18

Simple and best practice solution for 3(3x-9)-3=3(x-4)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-9)-3=3(x-4)+18 equation:



3(3x-9)-3=3(x-4)+18
We move all terms to the left:
3(3x-9)-3-(3(x-4)+18)=0
We multiply parentheses
9x-(3(x-4)+18)-27-3=0
We calculate terms in parentheses: -(3(x-4)+18), so:
3(x-4)+18
We multiply parentheses
3x-12+18
We add all the numbers together, and all the variables
3x+6
Back to the equation:
-(3x+6)
We add all the numbers together, and all the variables
9x-(3x+6)-30=0
We get rid of parentheses
9x-3x-6-30=0
We add all the numbers together, and all the variables
6x-36=0
We move all terms containing x to the left, all other terms to the right
6x=36
x=36/6
x=6

See similar equations:

| -w+195=248 | | 2t=t+6 | | 15x+10=5x-20 | | -15=5(3m-10)-5m | | 27=35-v | | (2x+24)+90=180 | | .2x+x=2500 | | 3s+1=s+15 | | −19=b−6 | | 10x+5=9x+5 | | 3u+29=u+39 | | 13-2(3x-1)=18-4(2x+1)+3x | | -16=|-4k| | | 26=38-x | | 9–2f=39 | | 5x2−3x-7=1 | | -2r-r=9 | | 5(x-6)=2(x+3$ | | F(-2)=9-3x | | 4x-9/7-1=6/5x | | 9–2f=3 | | (4-3x)(2+x)= | | x-88/9=3/5 | | 3(3x-2)-2x=15 | | -7+5u=13 | | 2(4i+2)=4i-12(i-1) | | 5/y+2=2/y+2+3 | | 16/4=y/4 | | 6w-60=2w | | 3k-16=-4 | | 10x-57=47 | | 5x+9=-93 |

Equations solver categories